Reproducibility and validity of workers’ self-reports of physical work demands - Stock, Susan R.; Fernandes, Rita; Delisle, Alain; Vézina, Nicole (Scandinavian Journal of Work, Environment & Health, 2005)
The objective of this paper is to provide a systematic review of the reproducibility and validity of self-report questions concerning physical work demands. After a bibliographic search of Medline and Ergonomic Abstracts for 1980–2003, 15 articles meeting the eligibility criteria were reviewed for methodological quality; 82 formulations of questions on physical work demands were evaluated for reproducibility and 83 for validity. Questions evaluated for both reproducibility and validity that performed well in both sets of studies included those on duration or presence of sitting and standing posture, the presence of walking, kneeling or squatting postures, duration or frequency of hands above shoulders, manual handling of more than or less than 10 kg, general level of physical effort, presence and duration of whole-body vibration, and duration of the use of visual display terminals. Suggestions for improving the design of reproducibility and validity studies and directions for future research in physical workload measurement are proposed.
Keywords: ergonomics; MSD; musculoskeletal disorder; physical work demand; questionnaire; reproducibility; review; self-assessment; self-report; systematic review; validity; worker; workload